A review of support tools to assess multi-sector interactions in the emerging offshore Blue Economy. Issue 133 (July 2022) - Turschwell, MP; Hayes, MA; Lacharité, M.; Abundo, M.; Adams, J.; Blanchard, J.; Brain, E.; Buelow, CA; Bulman, C.; Condie, SA; Connolly, RM; Dutton, I.; et al.
Abstract: Multiple ocean sectors compete for space and resources, creating conflicts but also opportunities to plan for synergistic outcomes that benefit multiple sectors. Planning and management are increasingly informed by qualitative and quantitative methods for assessing multi-sector interactions to identify trade-offs and synergies among sectors and with the environment, but there is a need to critically review the alignment of these tools with the requirements of Blue Economy stakeholders. Through a systematic literature review, an operational maturity analysis, and a survey of Blue Economy stakeholders, we found that the most well-developed tools for assessing interactions between multiple Blue Economy industries, and with the environment, are spatial prioritization tools, such as Marxan and multi-criteria decision support tools; and spatial static tools, such as cumulative effect mapping. More complex process/dynamic tools such as ecosystem and oceanographic models are well developed for single sectors, particularly water quality assessments and commercial fisheries, but have been less commonly applied in multi-sector contexts. Our review and stakeholder survey highlighted that assessing the environmental and operational suitability of sites for Blue Economy infrastructure in conjunction with operational impacts, trade-offs and decommissioning considerations requires: 1) a toolbox of approaches that covers a range of spatial, temporal and ecological scales; 2) tools that capture interactions and feedbacks among sectors, and with the environment, without being unnecessarily complicated (i.e., tractable to use and allow for effective communication of findings); and 3) continued synthesis of approaches and tools used across sectors such as commercial fishing, aquaculture, offshore renewable energy, and offshore engineering. Highlights: Competition for ocean space and access to its resources is rapidly increasing. We reviewed the tools to assess trade-offs between sectors and the environment. Cumulative effect mapping and spatial prioritization are commonly used tools. Ecosystem and dynamic models are less commonly applied in multi-sector contexts. A toolbox of approaches can support the management of multi-sector interactions.